STUDENT READINESS TOWARDS INTERPROFESSIONAL EDUCATION BASED ON THE HAJJ HEALTH - Wijaya, Dhani; Indradmojo, Christyaji; Novianto, Muhammad Rizal; Octavia, Rista; Wahid, Cep Reza Alam (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Interprofessional education (IPE) Faculty of Medicine and Health Science Maulana Malik Ibrahim State Islamic University (FKIK UIN MMI) were designed based on hajj health and involved prospective pilgrims (CJH) as the target. The program’s goal was to achieve collaboration among health students and support CJH to achieve the istitha’ah condition. Thus student readiness becomes one of the success parameters. This study aims to evaluate the readiness of FKIK UIN MMI students for the hajj health-based IPE program.Methods: Cross-sectional descriptive method was used with the FKIK UIN MMI students class 2018 as the population. Students who undertook the hajj health-based IPE program in 2021 were classified in the inclusion criteria. Meanwhile, the IPE participants that did not fill out the questionnaire were excluded. The questionnaire was adopted from the Readiness for Interprofessional Learning Scale and processed with Microsoft excel.Results: The readiness of 113 students was categorized as "very ready" on the aspect of collaboration and cooperation, also on the positive professional identity subject, with readiness levels of 83.36% and 81.23%, respectively. The percentage of readiness for the negative professional identity aspect was 48.20% and categorized as "quite ready". Professional roles and responsibilities had a score of 708, and were categorized as "ready".Conclusion: FKIK UIN MMI students had a good readiness level for the hajj health-based IPE program. Further studies are needed to examine the factors that emerge as barriers to joint learning between professions. The lecturer's readiness is needed to be evaluated as well.